Pancasila as Grundnorm and Islamic Religious Education as Ethical Foundation: Reconstructing National Economic Law through Islamic Sociological Jurisprudence Theory for Social Justice and Public Welfare - Hanifa Anan; Vera Dewi Saputri; Intan Noraziza Making; Ahmad Muhamad Mustain Nasoha (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research aims to analyze the urgency of reconstructing national economic law through the integration of Pancasila values as the grundnorm and the principles of Islamic law using the Islamic Sociological Jurisprudence Theory approach. This study is motivated by the tendency of Indonesia’s economic law to emphasize materialistic and individualistic orientations, which have not fully reflected the substantive justice mandated by Pancasila. The research employs a normative legal method with conceptual, philosophical, and sociological approaches, supported by library research for collecting legal materials. The findings reveal that Pancasila occupies a fundamental position as the basic norm of the national legal system, while Islamic law functions as a source of moral values that strengthens the law’s social legitimacy. The Islamic Sociological Jurisprudence Theory is considered relevant because it integrates normative, social, and spiritual dimensions in legal development. Empirical problems, including corruption, resource conflicts, and the growth of illegal online lending practices, indicate a gap between legal norms and social realities. Therefore, reconstructing national economic law is essential to establish a legal system that ensures legal certainty, promotes social justice, and advances public welfare (maslahah). The integration of Pancasila values and Islamic law is expected to create a more responsive, humane, and socially relevant legal framework.